Dual-In/Out strategy for genes integration into bacterial chromosome: a novel approach to step-by-step construction of plasmid-less marker-less recombinant E. coli strains with predesigned genome structure - Biryukova Irina V; Skorokhodova Aleksandra; Zimenkov Danila V; Gak Evgeny R; Minaeva Natalia I; Mashko Sergey V (BMC Biotechnology, 2008)
Abstract Background The development of modern producer strains with metabolically engineered pathways poses special problems that often require manipulating many genes and expressing them individually at different levels or under separate regulatory controls. The construction of plasmid-less marker-less strains has many advantages for the further practical exploitation of these bacteria in industry. Such producer strains are usually constructed by sequential chromosome modifications including deletions and integration of genetic material. For these purposes complex methods based on in vitro and in vivo recombination processes have been developed. Results Here, we describe the new scheme of insertion of the foreign DNA for step-by-step construction of plasmid-less marker-less recombinant E. coli strains with chromosome structure designed in advance. This strategy, entitled as Dual-In/Out, based on the initial Red-driven insertion of artificial φ80-attB sites into desired points of the chromosome followed by two site-specific recombination processes: first, the φ80 system is used for integration of the recombinant DNA based on selective marker-carrier conditionally-replicated plasmid with φ80-attP-site, and second, the λ system is used for excision of inserted vector part, including the plasmid ori-replication and the marker, flanked by λ-attL/R-sites. Conclusion The developed Dual-In/Out strategy is a rather straightforward, but convenient combination of previously developed recombination methods: phages site-specific and general Red/ET-mediated. This new approach allows us to detail the design of future recombinant marker-less strains, carrying, in particular, rather large artificial insertions that could be difficult to introduce by usually used PCR-based Recombineering procedure. The developed strategy is simple and could be particularly useful for construction of strains for the biotechnological industry.